Suppression of glioblastoma by a drug cocktail reprogramming tumor cells into neuronal like cells - Gao, Longfei (Sci Rep, 2019)
Glioblastoma (GBM) is the most common and aggressive malignant tumor in adult brain. Even with the current standard therapy including surgical resection followed by postoperative radiotherapy and chemotherapy with temozolomide (Temo), GBM patients still have a poor median survival. Reprogramming of tumor cells into non-malignant cells might be a promising therapeutic strategy for malignant tumors, including GBM. Based on previous studies using small molecules to reprogram astrocytes into neuronal cells, here we further identified a FTT cocktail of three commonly used drugs (Fasudil, Tranilast, and Temo) to reprogram patient-derived GBM cells, either cultured in serum containing or serum-free medium, into neuronal like cells. FTT-treated GBM cells displayed a neuronal like morphology, expressed neuronal genes, exhibited neuronal electrophysiological properties, and showed attenuated malignancy. More importantly, FTT cocktail more significantly suppressed tumor growth and prolonged survival in GBM patient derived xenograft than Temo alone. Our study provided preclinical evidence that the neuronal reprogramming drug cocktail might be a promising strategy to improve the existing treatment for GBM.